2005
DOI: 10.1017/s0954579405050169
|View full text |Cite
|
Sign up to set email alerts
|

Personal relatedness and attachment in infants of mothers with borderline personality disorder

Abstract: The principal aim of this study was to assess personal relatedness and attachment patterns in 12-month-old infants of mothers with borderline personality disorder~BPD!. We also evaluated maternal intrusive insensitivity toward the infants in semistructured play. We videotaped 10 mother-infant dyads with borderline mothers and 22 dyads where the mothers were free from psychopathology, in three different settings: a modification of Winnicott's Set Situation in which infants faced an initially unresponsive~"still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(159 citation statements)
references
References 68 publications
5
152
0
2
Order By: Relevance
“…In a recent series of studies involving infants of mothers with borderline personality disorder, again, 12-month-old infants of mothers with borderline personality disorder were just as likely to initiate shared attention with their mothers as were infants of nonborderline mothers (Meyer, Hobson, Beck, & Lyons-Ruth, 2006). This occurred even though these infants also were more likely to be disorganized in their attachments (Hobson, Patrick, Crandell, García-Pérez, & Lee, 2005) and the borderline parents were found to be more intrusive on a structured play task (Hobson, Patrick, Crandell, Perez, & Lee, 2004). In addition, the quality of affect in the dyad was more negative among those who did not initiate joint attention.…”
Section: Twelve Months: Sharing Orientations and Influencing Joint Atmentioning
confidence: 99%
“…In a recent series of studies involving infants of mothers with borderline personality disorder, again, 12-month-old infants of mothers with borderline personality disorder were just as likely to initiate shared attention with their mothers as were infants of nonborderline mothers (Meyer, Hobson, Beck, & Lyons-Ruth, 2006). This occurred even though these infants also were more likely to be disorganized in their attachments (Hobson, Patrick, Crandell, García-Pérez, & Lee, 2005) and the borderline parents were found to be more intrusive on a structured play task (Hobson, Patrick, Crandell, Perez, & Lee, 2004). In addition, the quality of affect in the dyad was more negative among those who did not initiate joint attention.…”
Section: Twelve Months: Sharing Orientations and Influencing Joint Atmentioning
confidence: 99%
“…Attachment research has provided evidence that when parents display frightened, frightening, or otherwise disrupted forms of affective communication with their infants, the infants may fail to develop an organized strategy for achieving comfort from their caregivers and instead show contradictory and disorganized approach-avoidance behavior toward the parent (Lyons-Ruth, Bronfman, & Parsons, 1999;. Recently, infants of mothers with BPD have also been reported to display a high prevalence of disorganized attachment (80%) (Hobson, Patrick, Crandell, Garcia-Perez, & Lee, 2005). Other studies of infants with disorganized attachments indicate that by 3 -5 years old, many previously disorganized infants reorganize their attachment behaviors into either a controlling -punitive attachment pattern (hostile or humiliating behavior towards parent) or a controlling-caregiving pattern (helping, Borderline and dysthymic women 3 protecting, worrying about the parent; Main, Kaplan, & Cassidy, 1985;NICHD Early Child Care Research Network, 2001;Wartner, Grossmann, Fremmer-Bombik, & Suess, 1994).…”
Section: Attachment Representations Of the Bpd Patientmentioning
confidence: 99%
“…Disorganized attachment in infancy has also been shown to be related to mothers' HH states of mind; states of mind which the current report also finds more prevalent among BPD women . Finally, recent studies of mothers with BPD have revealed intrusive insensitivity with their own infants at 2 months and 12 months of age (Crandell, Patrick, & Hobson, 2003;Hobson et al, 2005).…”
mentioning
confidence: 98%
“…However, it would be misleading to suggest that borderline personality disorder causes the behaviour, since so many mothers with borderline personality disorder do not abuse their children in this way. Nevertheless, borderline personality disorder is associated with a variety of parenting problems (Hobson et al, 2005), almost certainly mediated through the attachment style of affected mothers. Behaviours associated with borderline personality disorder, including selfharm and minor forensic behaviours such as shoplifting, have been found in individuals who fabricate or induce illness in children in their care.…”
Section: Psychiatric Illness and Personality Disordermentioning
confidence: 99%